(3VhA GdeUHGMs - (3JGL GdOjf eMeO Hf eMeO Hf CMeO GdCSaQGjjfjs; (3GdeWQRj , HQgGf GdOjf CHh GdaJM,J (B610 (3g` s ((3UGdM Hf NhGLg s)
(3ChdgG (B:s
(3CeG HYO, aEf fhY GdCOH Ydi cKQI TLhfg, hJTYH afhfg, fhY YR Ydi GdWdHI eQGeg s
(3BNQgG (B:s
(3hgPG HGH ddEWfGH ajg eLGd, dcfg jaVj Edi GdedGd, aGbJUQJ Ydi GdbOQ s
(3GdeUHGM dfGUQ Hf YHOGdSjO GdeWQRj GdeJhai (B610(3g`s
(3HgG fXGe GdJYbjHIs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs